Преобразуйте в многочлен выражение: 1)-(v - 5)^3 - (v + 2)(v + 3)

2) (x - 4)^2 - 2(x + 1)(x + 4)

3) (a + 3)^3 + (a + 1)(a + 4)

2

Ответы и объяснения

Лучший Ответ!
2012-03-24T13:27:20+00:00

1) вроде так..     

= -(v^3-15v^2+75v-75)-(v^2+3v+2v+6)=-v^3+15v^2-75v+75-v^2-3v-2v-6= -v^3+14v^2-80v+69

2)  

= x^2-8x+16-2^x-8x-2x-8=x^2-18x-8

3)

=a^3+9a^2+27a+9+9a^2+4a+a+4=a^3+10a^2+32a+13

 

2012-03-24T13:34:05+00:00

1)-(v - 5)^3 - (v + 2)(v + 3) =-(v^3-15v^2+75v-125)-(v^2+3v+2v+6)=- v^3 +15v^2 -75v+125-v^2-3v-2v-6=-v^3+9v^2-75v+125 
2) (x - 4)^2 - 2(x + 1)(x + 4)=x^2-8x+16-2(x^2+4x+x+4)=x^2-8x+16-2x^2-10x-8=-x^2-18x+8
3) (a + 3)^3 + (a + 1)(a + 4)=a^3+9a^2+27a+27+a^2+4a+a+4=a^3+10a^2+32a+31